Alaska Dreams - Snow, Jennifer; Snow, Jennifer; Snow, Jennifer (Toronto, Ontario : HQN, 2022)
Is she making the right decision...for her career and her heart? Following a near-death experience, Selena Hudson is finally going after the career she wants. And since casting directors wont see her as anything but a rom-com queen, Selena signs on to produce and star in her own movie--an edgy psychological thriller. But just as the cast and crew arrive on location in Wild River, Alaska, the leading man drops out of the production. Reporter Gus Orosco is not hiding out in Wild River--hes waiting for the dust to settle after his on-camera "overreaction" triggered by watching his ex-fiancee get engaged to a superstar hockey player. Gus doesnt want to be anywhere near the film crew shooting at his familys campgrounds, but Selena makes him an offer he cant refuse: shell snag Gus an interview with Sports Beat if hell be her leading man. All Gus has to do is learn his lines, hit his marks and somehow ignore the sparks flying between them...even though theyre hot enough to melt the Alaskan snow. Bonus Novella Jade Frazier learns that Christmas is the season for second chances--in life as well as love--in Jennifer Snows An Alaskan Christmas Homecoming.
Keywords: Man-woman relationships -- Fiction; Alaska -- Fiction; Romance fiction